2011
DOI: 10.3390/coatings1010053
|View full text |Cite
|
Sign up to set email alerts
|

A Modified Surface on Titanium Deposited by a Blasting Process

Abstract: Hydroxyapatite (HA) coating of hard tissue implants is widely employed for its biocompatible and osteoconductive properties as well as its improved mechanical properties. Plasma technology is the principal deposition process for coating HA on bioactive metals for this application. However, thermal decomposition of HA can occur during the plasma deposition process, resulting in coating variability in terms of purity, uniformity and crystallinity, which can lead to implant failure caused by aseptic loosening. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 33 publications
1
25
0
Order By: Relevance
“…The graphs in Figure 5 are representative of a large range of XRD results obtained [18]. While the equipment used was not sensitive enough to examine the full range of peaks in the HA range the XRD data demonstrated that the most significant HA peaks in the spectra of the deposited coatings were identical to those of the powder material for both processes (JCPDF: XXXX).…”
Section: Coating Chemistry and Topographymentioning
confidence: 99%
“…The graphs in Figure 5 are representative of a large range of XRD results obtained [18]. While the equipment used was not sensitive enough to examine the full range of peaks in the HA range the XRD data demonstrated that the most significant HA peaks in the spectra of the deposited coatings were identical to those of the powder material for both processes (JCPDF: XXXX).…”
Section: Coating Chemistry and Topographymentioning
confidence: 99%
“…Titanium and titanium alloys are widely used as structural materials in fields such as the aerospace industry or automobile industry, due to their high melting point, low density, and their superior high-temperature mechanical properties [1][2][3][4][5]. However, the maximum temperature at which the alloys can be used is 873 K, above which the mechanical properties will be reduced and the life of the alloys seriously affected.…”
Section: Introductionmentioning
confidence: 99%
“…These methods are used for auto parts and various kinds of mechanical parts. On the other hand, thermal-sprayed coatings [8] or blasting process [9] can make additional layers using different material from the base metal to get higher hardness, wear resistance, thermal resistance, or corrosion resistance.…”
Section: Introductionmentioning
confidence: 99%